Praxis - Handeln und Handelnde in antiker Philosophie: Akten des 6. Kongresses der Gesellschaft für antike Philosophie 2019 - Buddensiek, Friedemann; Odzuck, Sebastian (Beiträge zur Altertumskunde, 2023)
The papers in this volume provide insights into the diverse discussions surrounding questions of agent and action theory in ancient philosophy, from the fifth century BCE up into late antiquity. It focuses on factors relevant to action such as the soul; the relationship between agents, actions, and goals; the rationality relevant to action; and taking action in the community